Phytochemical and biological evaluation of Albizia richadiana (Benth. Fabaceae family) - Shetu, Hosne Jahan (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015